Clinical-effectiveness of self-management interventions in chronic obstructive pulmonary disease: An overview of reviews. (August 2017) - Murphy, Linda A; Harrington, Patricia; Taylor, Stephanie JC; Teljeur, Conor; Smith, Susan M; Pinnock, Hilary; Ryan, Máirín
Self-management (SM) is defined as the provision of interventions to increase patients' skills and confidence, empowering the individual to take an active part in their disease management. There is uncertainty regarding the optimal format and the short- and long-term benefits of chronic obstructive pulmonary disease (COPD) SM interventions in adults. Therefore, a high-quality overview of reviews was updated to examine their clinical effectiveness. Sixteen reviews were identified, interventions were broadly classified as education or action plans, complex interventions with an SM focus, pulmonary rehabilitation (PR), telehealth and outreach nursing. Systematic review and meta-analysis quality and the risk of bias of underlying primary studies were assessed. Strong evidence was found that PR is associated with significant improvements in health-related quality of life (HRQoL). Limited to moderate evidence for complex interventions (SM focus) with limited evidence for education, action plans, telehealth interventions and outreach nursing for HRQoL was found. There was strong evidence that education is associated with a significant reduction in COPD-related hospital admissions, moderate to strong evidence that telehealth interventions and moderate evidence that complex interventions (SM focus) are associated with reduced health care utilization. These findings from a large body of evidence suggesting that SM, through education or as a component of PR, confers significant health gains in people with COPD in terms of HRQoL. SM supported by telehealth confers significant reductions in healthcare utilization, including hospitalization and emergency department visits.